Factors Influencing Students’ Difficulties in Writing an Argumentative Text in Senior High School - Isnawati, Uzlifatul Masruroh (Universitas Batanghari Jambi, 2025)
The ability to write argumentative text is one of the important skills that requires students to express ideas in a logical and convincing manner. However, many students difficulties in writing this text. This study aims to analyze the factors that causes of difficultiesby grade XI students of MAN 1 Lamongan in writing argumentative texts. Data were collected through closed questionnaires. This data analysis techniques used a qualitative descriptive. The results showed that students experienced various difficulties in writing argumentative texts. The factors that influence the difficulties are divided into three main categories, namely psychological factors (46%), sociocultural factors (44.8%), and linguistic factors (46.2%). Linguistic factors are the most dominant factor in causing students' difficulties. Based on these findings, it can be concluded that students experience many difficulties in writing argumentative texts, it is recommended that the teaching of writing is focused on improving understanding of language structure and sentence structure in argumentative texts.